An Open Trial of Electronic Cigarettes for Smoking Cessation Among Methadone-Maintained Smokers - Stein, Michael D. (Nicotine Tob Res, 2016)
INTRODUCTION: Smoking cessation pharmacotherapies tested in persons with opioid use disorder have produced low quit rates. Electronic cigarettes (e-cigarettes) have been used by many methadone-maintained (MMT) smokers, but controlled trials evaluating cessation and reduction outcomes have not been performed in this population with deleterious tobacco-related health consequences. METHODS: In this open trial of NJOY e-cigarettes, MMT smokers received 6 weeks of treatment and were instructed to use only e-cigarettes. Outcomes included carbon monoxide confirmed 7-day point smoking cessation prevalence at week 7 (end of treatment) and self-reported change in mean cigarettes per day (CPD) at each 2-week assessment. The final assessment was 2 weeks after treatment ended (week 9). RESULTS: The 12 participants averaged 46 years old and 50% were male. On average, participants reported smoking 17.8 (±5.3) CPD. One person had a biochemically confirmed quit at week 7. Participants tended to report marked reductions in mean CPD between quit day (week 1) and the week 3 assessment. Relative to baseline, statistically significant reductions in mean CPD were observed at all follow-up assessments. Mean reductions in CPD were −12.4 (95% confidence interval [CI]: −15.0, −9.9; P < .001), −14.8 (95% CI: −17.4, −12.2; P < .001), −13.9 (95% CI: −16.6, −11.2), and −10.8 (95% CI: −13.4, −8.2; P < .01) at the 3-, 5-, 7-, and 9-week assessments, respectively. Adherence to e-cigarettes was 89.1% during the 6 treatment weeks. CONCLUSIONS: E-cigarettes were associated with reductions in cigarette use. Smoking cessation rates in MMT smokers are low and whether long-term smoking reductions can persist and produce health benefits should be studied. IMPLICATIONS: E-cigarettes were associated with reduced tobacco use in MMT smokers. Adherence to e-cigarettes is high among methadone smokers. Week-7 smoking quit rates are similar to pharmacotherapies tested in this population.